Light scattering properties of peptone solution - Kotsyumbas, Ihor; Bilyy, Oleksandr; Getman, Vasyl; Kotsyumbas, Halyna; Kushnir, Ihor (Видавництво Львівської політехніки, 2010)
The results of researches of light scattering properties of peptone liquid solution for the bacterial cells of Escherichia coli is described.
Keywords: bacteria; solution; peptone; light scattering